Barney Wakuri, Warren Creek Plains, Northern Territory, 1974 - Rhodes, Jon, 1947- (1974)
Barney Wakuri holding a kangaroo joey.
Title from caption list.
Part of: Australia, 1977.
Also available online
Keywords: Wakuri, Barney -- Photographs; Aboriginal Australians -- Northern Territory -- Warren Creek -- Photographs; Animals - Mammals - Marsupials - Kangaroos / Wallabies; Warren Creek (South Central NT SF52-16)